Ministérios não-ordenados : gênese histórica, experiências e reflexões - Royer, Luciano (2014)
The paper characterizes the historical genesis, nature and disposition of non-ordained ministries in the Catholic Church. The research aims to present some theological and historical features of the theological-dogmatic core of the vocation and mission of the laity in the Catholic Church's mission. The object of study are texts of the New Testament Documents Conciliar texts and synthesis of Episcopal Conferences of Latin America. The documents indicate specifics of each season, with their contexts and updates the understanding on the participation of the laity in evangelization.